Gut Microbiota as Environmental Modulators of Hormonal Balance in Women: A Systematic Review of Probiotic Interventions in PCOS - Entesar Mohamed; Maysim Mustafa (المجلة الأفروآسيوية للبحث العلمي, 2025)
Gut microbiota is recognized emerging evidence as a putative environmental controller of hormonal balance in women, especially in polycystic ovary syndrome (PCOS). This is a review of the current clinical evidence, focusing on recent studies that have determined the effects of multi-strain probiotics on endocrine profiles and body mass index (BMI) in PCOS patients. Although promising with outcomes such as TSH, SHBG, and Free Androgen Index (FAI) changes, the primary limitations of short study duration, population size, and lack of microbiota profiling negate the interpretability. The article brings to light the need for mechanistic insights, stratified probiotic interventions, and large-scale research to validate the microbiome-hormone axis as a viable therapeutic target. Recent advances in microbiome science suggest that dysbiosis of the gut may be involved in many metabolic and hormonal dysregulations seen in PCOS. Probiotic supplementation, particularly with multi-strain formulations, has shown promise in reducing androgen levels, enhancing insulin sensitivity, and enhancing markers of endocrine function. In addition, heterogeneity of dosage, duration, and strains poses a major barrier to generalization. Second, the absence of routine gut microbiota profiling in the majority of clinical trials limits our understanding of strain-specific mechanisms and concomitant biological determinants. Because PCOS is a multi-factorial condition, future studies must adopt integrative approaches combining metagenomics, metabolomics, and endocrinology to tailor probiotic treatment. Overall, current evidence projects a robust but incomplete picture of therapeutic promise for gut microbiota modulation in the treatment of PCOS.